Sinergi Komunitas dalam Mendorong Akselerasi Pengembangan BUMDes Damai Mandiri berbasis Kearifan Lokal: Indonesia - Yesayabela, Tito Mariano; Agustian, Aditiya Tri; Lubis, Lunariana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Village-Owned Enterprises (BUMDes) are strategic instruments for village economic independence, yet faced with a paradox between the ideal potential and the reality of failure in the field, which is often caused by the "capacity gap" and low participation. This research aims to uncover the "black box" of how the process of community synergy and local wisdom are operationalized in daily management practices to encourage acceleration of BUMDes. This research uses a descriptive qualitative method with a case study approach on BUMDes Damai Mandiri. The research stages included data collection through in-depth interviews, participatory observation, and documentation studies, which were then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results and discussion show that the acceleration of BUMDes is not caused by a single factor, but rather by a holistic community synergy model. This model is built on four mutually reinforcing components: (1) solid social capital foundation (trust, network, and local wisdom such as deliberation); (2) authentic Community-Based Development (CBD) process (full participation and utilization of local assets such as Etawa goats); (3) adaptive BUMDes institutional container (dialectical structure-agency interaction); and (4) institutional rational choice-based motivation (multi-layered incentive design).